PENGARUH PERIKLANAN TERHADAP MINAT BELI KONSUMEN TOKOPEDIA DI KOTA PALEMBANG - Naruliza, Esty; Laleno, Elsye Afrincia (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2020)
The development of business through internet media is increasing, along with the increasing of Internet users in the world especially in Indonesia. Advertising is a factor that is quite important in attracting the Purchace interest of the consumer in this research is Tokopedia in the city of Palembang. Advertising is any form of non-personal communication and promotion of ideas, products or services that are paid for by certain sponsors or that have not yet been identified in order to create consumer buying interest. While buying interest is the tendency of consumers to buy a brand or take actions related to the purchase. In this research, the object of research is Tokopedia consumers in Palembang. The sampling method uses accidental sampling. The data used are primary data by distributing questionnaires directly to Tokopedia application users in the city of Palembang. the number of samples was 349 respondents. The test is carried out in three stages, namely the validity and reliability test, the classic assumption test and the hypothesis test The results of this research indicate that advertising has a positive effect on consumer buying interest of Tokedia in Palembang, it can be seen from the regression test results Y = 4,571 + 0.821 + e. If seen from the coefficient of determination (R2) of 80% consumer buying interest can be explained by advertising. While 20% is influenced by other variables not examined in this research such as discounts, brand image, price, availability of goods and others.